Genomic and chromatin features shaping meiotic double-strand break formation and repair in mice - Yamada, Shintaro (Cell Cycle, 2017)
The SPO11-generated DNA double-strand breaks (DSBs) that initiate meiotic recombination occur non-randomly across genomes, but mechanisms shaping their distribution and repair remain incompletely understood. Here, we expand on recent studies of nucleotide-resolution DSB maps in mouse spermatocytes. We find that trimethylation of histone H3 lysine 36 around DSB hotspots is highly correlated, both spatially and quantitatively, with trimethylation of H3 lysine 4, consistent with coordinated formation and action of both PRDM9-dependent histone modifications. In contrast, the DSB-responsive kinase ATM contributes independently of PRDM9 to controlling hotspot activity, and combined action of ATM and PRDM9 can explain nearly two-thirds of the variation in DSB frequency between hotspots. DSBs were modestly underrepresented in most repetitive sequences such as segmental duplications and transposons. Nonetheless, numerous DSBs form within repetitive sequences in each meiosis and some classes of repeats are preferentially targeted. Implications of these findings are discussed for evolution of PRDM9 and its role in hybrid strain sterility in mice. Finally, we document the relationship between mouse strain-specific DNA sequence variants within PRDM9 recognition motifs and attendant differences in recombination outcomes. Our results provide further insights into the complex web of factors that influence meiotic recombination patterns.